Psychosocial management of diabetes: Applicability of national guidelines to Mewat, an underserved region of Haryana - Kumar, Arun; Goel, Pawan K.; Vashisht, Brij M.; Mittal, Kundan (Journal of Social Health and Diabetes, 2014)
Mewat, a district of Haryana state in India, has unique and different socio cultural milieu which can limit the effective implementation of national guidelines on psychosocial management of diabetes. We reviewed and discussed the underlying socio-cultural and demographic characteristics of Mewat district in order to tailor these national guidelines according to the applicability to improve implementation. We also proposed possible multifaceted interventions/solutions to overcome the potential hurdles for successful implementation of the guidelines in the district.
Keywords: Diabetes; guidelines; India; management; Mewat; psychosocial; recommendations